2006
DOI: 10.1063/1.2358190
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in metal-mixed ion-implanted polymer films

Abstract: Articles you may be interested in Preparation of metal mixed plastic superconductors: Electrical properties of tin-antimony thin films on plastic substrates

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…18 As part of an on-going effort to learn how to tune the properties of these systems, we have performed studies on the electrical properties of these systems prior to metal mixing. We have shown that the electrical properties of metallic thin films are remarkably robust to variations in the substrate morphology.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…18 As part of an on-going effort to learn how to tune the properties of these systems, we have performed studies on the electrical properties of these systems prior to metal mixing. We have shown that the electrical properties of metallic thin films are remarkably robust to variations in the substrate morphology.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been shown that metal mixed superconducting polymers with a metallic normal state can be produced, their residual resistivity ratios defined as ͑300 K͒ / ͑T c + ͒, where ͑T c + ͒ is the resistance at a temperature slightly above the superconducting transition, are extremely small ͑ϳ1.2͒, indicating that these are extremely disordered systems. 18 This is not unexpected given the manner in which these materials are produced. What is unexpected is the observation that both the critical temperature T c and the critical field B c are lower than that of the unimplanted metal film ͑compare Ref.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations